Toxicological Evaluation Of Calotropis Procera (CALP) In Wistar Rats: Acute And Sub-Acute Studies - Yatendra Singh; Madan Kaushik (Revista Electronica de Veterinaria)
Calotropis procera (CALP), belonging to the family Apocynaceae, is a well-known medicinal plant distributed in tropical and subtropical regions. It has been extensively used in Ayurveda and folk medicine for the treatment of ailments such as fever, inflammation, asthma, skin disorders, and digestive disturbances. Despite these applications, the plant is notorious for its toxic properties, primarily attributed to the presence of cardenolides (cardiac glycosides), alkaloids, terpenoids, and other bioactive secondary metabolites. The duality of its therapeutic potential and toxic nature makes it essential to evaluate its safety profile. The present experimental study investigates the acute and sub-acute oral toxicity of CALP root extracts in Wistar rats, adhering to OECD guidelines. In the acute toxicity study, no mortality was observed up to 2000 mg/kg; however, the LD₅₀ was determined to be 3000 mg/kg using the Karber method. In the sub-acute 28-day study, dose-dependent alterations were observed in hematological, biochemical, and histopathological parameters. At higher doses (1000–2000 mg/kg), CALP significantly decreased hemoglobin, red blood cell (RBC) counts, and platelet levels. Biochemical analysis revealed marked increases in glucose, serum creatinine, blood urea nitrogen (BUN), alkaline phosphatase (ALP), aspartate aminotransferase (AST), and bilirubin concentrations. Histopathological studies confirmed organ-specific toxicity, including hepatocyte degeneration and necrosis in the liver, gastric mucosal erosion in the stomach, and renal tubular degeneration and necrosis in the kidney. The heart tissue, however, appeared normal across all doses. The findings suggest that CALP is relatively safe at low doses (≤500 mg/kg), but its toxicity becomes evident at higher doses, particularly affecting the liver, kidney, and stomach. These results highlight the importance of cautious use of CALP in traditional medicine and emphasize the need for dose standardization and further mechanistic studies.